Front/back office considerations in the operational access to long-term care for older people: Findings of a multiple case study. (November 2013) - Schipper, Lisette; Meijboom, Bert; Luijkx, Katrien; Schols, Jos
Abstract : Background: Organizations that provide long-term care in the Netherlands are reconsidering the operational access to their services. Principles of operations management, such as front/back office configurations, might improve the redesign of operational access. Once a client gains entrance to the organization, direct interaction between client and care provider starts. This is a front office activity. In this paper, we address the question: How are front/back office aspects recognisable in the operational access to long-term care for independently living elderly? Methods: We conducted a multiple case study ( n  = 4). Data gathering involved observations, interviews, and examination of documents. Transcripts of observations and interviews were coded and analyzed. Results: None of the studied entrance units were physically accessible. In all four cases a lot of administrative tasks were present, even with employees dedicated to front office tasks. By organizing separate entrance units, the cases decouple the access process from delivery of care. However, they subsequently couple all entrance-related activities in one job, i.e. a care advisor dedicated to a client. Conclusion: The case organizations organized their operational access process in separate units. Front/back office aspects were recognizable; however, seem not to have been considered consciously during the design of the access process.